Cysteine restriction-specific effects of sulfur amino acid restriction on lipid metabolism - Nichenametla, Sailendra N; Mattocks, Dwight A L; Cooke, Diana; Midya, Vishal; Malloy, Virginia L; Mansilla, Wilfredo; Øvrebø, Bente; Turner, Cheryl; Bastani, Nasser E; Sokolová, Jitka; Pavlíková, Markéta; Richie, John P; et al. (Aging cell, 2022)
Decreasing the dietary intake of methionine exerts robust anti-adiposity effects in rodents but modest effects in humans. Since cysteine can be synthesized from methionine, animal diets are formulated by decreasing methionine and eliminating cysteine. Such diets exert both methionine restriction (MR) and cysteine restriction (CR), that is, sulfur amino acid restriction (SAAR). Contrarily, SAAR diets formulated for human consumption included cysteine, and thus might have exerted only MR. Epidemiological studies positively correlate body adiposity with plasma cysteine but not methionine, suggesting that CR, but not MR, is responsible for the anti-adiposity effects of SAAR. Whether this is true, and, if so, the underlying mechanisms are unknown. Using methionine- and cysteine-titrated diets, we demonstrate that the anti-adiposity effects of SAAR are due to CR. Data indicate that CR increases serinogenesis (serine biosynthesis from non-glucose substrates) by diverting substrates from glyceroneogenesis, which is essential for fatty acid reesterification and triglyceride synthesis. Molecular data suggest that CR depletes hepatic glutathione and induces Nrf2 and its downstream targets Phgdh (the serine biosynthetic enzyme) and Pepck-M. In mice, the magnitude of SAAR-induced changes in molecular markers depended on dietary fat concentration (60% fat >10% fat), sex (males > females), and age-at-onset (young > adult). Our findings are translationally relevant as we found negative and positive correlations of plasma serine and cysteine, respectively, with triglycerides and metabolic syndrome criteria in a cross-sectional epidemiological study. Controlled feeding of low-SAA, high-polyunsaturated fatty acid diets increased plasma serine in humans. Serinogenesis might be a target for treating hypertriglyceridemia.
Keywords: Animals; cystein; Female; ženské pohlaví; průřezové studie; Obesity; serin; Methionine; lidé; Lipid Metabolism; Mice; Amino Acids, Sulfur; myši; metabolismus lipidů; aminokyseliny sírové; Cross-Sectional Studies; obezita; Male; Cysteine; methionin; Serine; zvířata; mužské pohlaví; Humans